Mendesain Cyber Security Core Banking System untuk Keamanan Menggunakan Firewall Pada PT. Bank Syariah Indonesia Tbk - Muhammad Kevin Meidiandra; Yulia Permata Sari; Tata Sutabri (Syntax Idea)
The increasingly advanced technology in banking services can provide convenience for customers in conducting transactions. Based on our research, the network using a firewall consists of several stages: activation and threat identification, firewall type selection, network segmentation, security testing and attack simulation, and evaluation and improvement. In this regard, Indonesian Islamic banks can enhance their cybersecurity by implementing a firewall as one of the critical defense layers in their IT infrastructure to protect against cyber threats and ensure the security of their systems.